2001
DOI: 10.1002/1521-3757(20010917)113:18<3555::aid-ange3555>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

A Free-Energy Relationship between the Rate of Acidic Hydrolysis of Glycosides and the pKa of Isofagomines

Abstract: Eine neue Antwort auf eine hundert Jahre alte Frage – warum Galactoside schneller hydrolysiert werden als Glucoside – wird hier gegeben. Dieses unterschiedliche Verhalten wurde lange darauf zurückgeführt, dass axiale OH‐Gruppen Konformationsänderungen auf dem Weg zum Übergangszustand erleichtern. Doch die hier vorgestellten Ergebnisse sprechen dafür, dass Unterschiede in der elektronenziehenden Wirkung (Pfeile) äquatorialer (A) und axialer OH‐Gruppen (B) entscheidend sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…It appears that there is a certain inconsistency between this result and the comprehensive programmable approach which showed benzylidene derivatives to be more reactive than their disarmed counterparts. Although a direct investigation of these two findings is not yet available, studies reported by Bols [63] offer the explanation that the disparity could be simply explained by the benzylidene orientation; axial –galactose (Wong et al) vs equatorial – glucose (Demchenko et al).…”
Section: Superdisarmed Building Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that there is a certain inconsistency between this result and the comprehensive programmable approach which showed benzylidene derivatives to be more reactive than their disarmed counterparts. Although a direct investigation of these two findings is not yet available, studies reported by Bols [63] offer the explanation that the disparity could be simply explained by the benzylidene orientation; axial –galactose (Wong et al) vs equatorial – glucose (Demchenko et al).…”
Section: Superdisarmed Building Blocksmentioning
confidence: 99%
“…A model study of the relative pK a values for protonated heterocyclic amines showed that equatorial substituents are significantly more deactivating than their axial counterparts (compare 67 and 68 in Fig. 5) [63]. Further revealed by these findings was that a perturbation of the equilibrium between ring conformations may also occur upon protonation of the heterocyclic amine [68].…”
Section: Superarmed Building Blocksmentioning
confidence: 99%
“…This reflects the higher ability of the electron withdrawing equatorial substituent to destabilize a positive charge at the anomeric position, as extensively investigated by the Bols group. 431,432 Scheme 128. Formation of 1,3-difluorinated 2-azidohexopyranoses based on a DAST-induced 1®6 migration process.…”
Section: Fluorination At Positions 1 Andmentioning
confidence: 99%
“…In addition, over the recent years there has been a noticeable shift in focus of the mechanistic glycosylation chemistry field toward studying stereoelectronics and conformation of the starting material and key reaction intermediates. ,,,,,,,,,,, While the stereoelectronic and conformational effects on reactivity have been studied extensively, the impact of these effects on stereoselectivity remains elusive. Although some model studies helped to establish general trends, ,, ,, practical application of the conformational factors to stereocontrol of glycosylation is still limited.…”
Section: Traditional Manual Synthesis Of Oligosaccharidesmentioning
confidence: 99%